Martín Vizcarra Cornejo in power: the alleged acts of corruption against him and his fight against corruption - Lovón Cueva, Marco Antonio (2020)
This research presents an analysis of Martín Vizcarra as a political actor in the framework of the political and judicial consequences related to the corruption issue he is accused of, first, as regional governor of Moquegua (2011-2014), then as Minister of Transport and Communications of Peru (2016-2017), and, later, as the highest authority of the country (2018-2021). Methodologically, the information obtained from journalistic documentation and statistics is used. The work points out that Vizcarra strategically builds a political identity with which he opposes corruption and with which he counteracts accusations or denunciations of crimes during his different actions against the Peruvian public administration in order to favor his image as a politician.